The functions, disease-related dysfunctions, and therapeutic targeting of neuronal mitochondria - Gribkoff, Valentin K.; Jonas, Elizabeth A.; Hardwick, J. Marie (Hoboken, New Jersey : John Wiley & Sons, 2015)
This book presents advances in the field of neuronal mitochondria - functions, relation to therapeutics, and pharmacology. For scientists and researchers in both industry and academia, this book provides detailed discussion, examples, and approaches, to illustrate the potential of mitochondria as therapeutic targets for neuronal diseases.- Helps readers understand the regulation of mitochondrial cellular processes, such as substrate metabolism, energy production, and programmed versus sporadic cell death- Offers insights on the development of strategies for targeted therapeutic approaches and potential personalized treatments- Includes examples of mitochondrial drugs, development, and mitochondria-targeted approaches for more efficient treatment methods and further developments in the field- Covers the model systems and approaches needed for the development of new drugs for the central nervous system to provide potential modern therapeutics for neurodegenerative disorders.
Mitochondrial permeability transition : look from a different angle / N. Brustovetsky -- The mitochondrial permeability transition pore, the c-subunit of the F1Fo ATP synthase, cellular development and synaptic efficiency / E.A. Jonas, G.A. Porter, Jr., G. Beutner, N. Mnatsakanyan and K.A. Alavian -- Mitochondrial channels in neurodegeneration / P.M. Peixoto, K.W. Kinnally and Evgeny Pavlov -- Mitochondrial Ca2+ transport in the control of neuronal functions : molecular and cellular mechanisms / Y.M. Usachev -- AMP-activated protein kinase (AMPK) as a cellular energy sensor and therapeutic target for neuroprotection / P. Weisova, S. Pfeiffer and J.H.M. Prehn -- HDAC6 : a molecule with multiple functions in neurodegenerative diseases / Y. Yan and R. Jiao -- Neuronal mitochondrial transport / A.L. Knight, Y. Chen, T. Sun and Z.-H. Sheng -- Mitochondria in control of hypothalamic metabolic circuits / C.M. Nasrallah and T.L. Horvath -- Mitochondria anchored at the synapse / G.A. Spirou, D. Jackson and G.A. Perkins -- Neuronal mitochondria are different : relevance to neurodegenerative disease / S.B. Berman and J.M. Hardwick -- PINK1 as a sensor for mitochondrial function : dual roles / E.K. Steer, M.K. Dail and C.T. Chu -- A get-together to tear it apart : the mitochondrion meets the cellular turnover machinery / G.-L. McLelland and E.A. Fon -- Mitochondrial involvement in neurodegenerative dementia / L. Bonanni, V. Frazzini, A. Thomas and M. Onofrj -- Neuronal mitochondria as a target for the discovery and development of new therapeutics / V.K. Gribkoff -- Mitochondria as a therapeutic target for Alzheimer's disease / C.H.-L. Hung, S.S.-Y. Chung, S.M.-Y. Lee and R.C.-C. Chang -- Mitochondria in Parkinson disease / G. Arena and E.M. Valente -- Therapeutic targeting of neuronal mitochondria in brain injury / H.M. Yonutas, E.D. Hall and P.G. Sullivan -- The use of fibroblasts from patients with inherited mitochondrial disorders for pathomechanistic studies and evaluation of therapies / D. Soiferman and A. Saada.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Mitochondrial pathology; Mitochondria -- Formation; Nervous system -- Diseases -- Treatment; Mitochondria -- Formation; Mitochondrial pathology; Nervous system -- Diseases -- Treatment; SCIENCE / Life Sciences / Biochemistry; Electronic books